Quality evaluation of minoxidil topical solutions obtained from magistral pharmacies - Karen N. Dartora; Paula C. Bona; Francielli L. dos Santos; Paula Bianchetti; Renata Vidor Contri (Drug Analytical Research, 2019)
The objective of this study was to evaluate quality parameters of magistral topical solutions containing minoxidil (A, B and C), comparing the results with the ones obtained for the industrial formulation. Organoleptic tests, evaluation of the pH and density, centrifuge test, drug content determination, comparison of indicated dosages and in vitro follicular penetration of minoxidil were performed. Regarding the organoleptic properties, differences in color and viscosity were observed between the magistral (composed of minoxidil sulfate) and the industrial formulations (composed of minoxidil base). For pH values, the magistral solutions presented considerably more acidic pH, compared to the industrial sample. For the density test, the samples with the highest ethanol percentages (B and C) presented lower density. In the centrifuge test, none of the samples showed changes. Considering the drug content test, only the industrial sample and the magistral sample C showed drug percentage within the expected (90-110%), indicating lack of correction factor determination by the magistral pharmacies. Furthermore, it was observed that the dosage indicated by the magistral pharmacies do not correspond to the dose indicated by the industry, being significantly lower. All topical solutions tested presented hair follicle penetration of minoxildil, without statistical difference. The results indicate that there is a failure in the magistral pharmacies regarding the production and the indication of dosage of minoxidil topical solutions.